Knowledge and Profanation: Transgressing the Boundaries of Religion in Premodern Scholarship - Mulsow, Martin (Intersections Ser., 2019)
Intro -- Contents -- Notes on the Editors -- Notes on the Contributors -- Introduction -- Part 1 The Sacred and the Profane in Art, Literature and Parody -- Chapter 1 Lucian of Samosata on Magic and Superstition -- Chapter 2 Rabbi Lazarus and the Rich Man: A Talmudic Parody of the Late Roman Hell (Yerushalmi Hagigah 2.2, 77d and Sanhedrin 6.9, 23c) -- Chapter 3 Cardinal Gabriele Paleotti's Call for Reform of Christian Art -- Chapter 4 The Sacred Becomes Profane - The Profane Becomes Sacred: Observations on the Desubstantialisation of Religious Discourse in the Early Modern Age -- Part 2 Early Modern European Knowledge about Pagan Religion -- Chapter 5 The Seventeenth Century Confronts the Gods: Bishop Huet, Moses, and the Dangers of Comparison -- Chapter 6 The Eleusinian Mysteries in the Age of Reason -- Part 3 Crossing the Boundaries in Biblical Scholarship: Ancient Preconditions and Early Modern Conflict -- Chapter 7 Athens and Jerusalem? Early Jewish Biblical Scholarship and the Pagan World -- Chapter 8 Richard Simon and the Charenton Bible Project: The Quest for 'Perfect Neutrality' in Interpreting Scripture -- Chapter 9 The Devil in the Details: The Case of Hermann Samuel Reimarus (1694-1768) -- Part 4 Scientific Knowledge and Religion -- Chapter 10 Cry Me a Relic: The Holy Tear of Vendôme and Early Modern Lipsanomachy -- Chapter 11 The Powerlessness of the Devil: Scientific Knowledge and Demonology in Clemente Baroni Cavalcabò (1726-1796) -- Index Nominum.